Sarecycline treatment for acne vulgaris: Rationale for weight‐based dosing and limited impact of food intake on clinical efficacy. Issue 3 (30th December 2021) - Grada, Ayman; Del Rosso, James Q.; Graber, Emmy; Bunick, Christopher G.; Stein Gold, Linda; Moore, Angela Y.; Baldwin, Hilary; Obagi, Zaidal; Damiani, Giovanni; Carrothers, Timothy; McNamee, Brian; Hanze, Eva
Abstract: Tetracycline‐class antibiotics are frequently prescribed by dermatologists, commonly for acne vulgaris. Gastrointestinal absorption of first and second‐generation tetracycline‐class antibiotics, including doxycycline and minocycline, may be reduced by co‐administration with food, resulting in potentially lower clinical efficacy. Development of novel compounds and formulations that are not impacted by diet could improve compliance, absorption, and effectiveness among patients. The objective of this study is to investigate weight‐based dosing protocols and the impact of food intake, including high‐fat meals, on the absorption, and clinical efficacy of sarecycline, a novel oral narrow‐spectrum third‐generation tetracycline‐class antibiotic approved by the Food and Drug Administration for acne vulgaris treatment. Data from 12 clinical studies were analyzed using population pharmacokinetic modeling, exposure–response modeling and pharmacodynamics to evaluate sarecycline dosing recommendations. The extent of exposure is estimated to decrease by 21.7% following co‐administration of a sarecycline tablet with a high‐fat meal. Based on the PopPK‐PD model, this is equivalent to a decrease in efficacy of 0.9 inflammatory lesions, which is not clinically meaningful. Sarecycline can be administered using weight‐based dosing with or without food. Co‐administration with high‐fat food has a limited impact on clinical efficacy. The pharmacokinetics of oral sarecycline may provide added convenience and support ease of use and improved compliance for acne vulgaris patients.